PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIF INTEGRATED READING AND COMPOSITION TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI PADA SISWA KELAS IV SD N 1 PANGGANG - Sari, Yunita; Jupriyanto, Jupriyanto; Sabila, Adinda Putri (Universitas Muria Kudus, 2024)
The aim of this research is to obtain information on the effect of implementing the CIRC type cooperative learning model on narrative essay writing skills in fourth grade students at SD N 1 Panggang. The research method used in this research is an experimental method with the pre-experimental One Group Pretest-Posttest type. The sample in this research was all 24 students in class IV of SD N 1 Panggang using a total sampling technique. The data collection technique for this research uses tests with instrument validation techniques using expert reliability and validity tests. The initial data analysis technique in this study used a normality test and final data analysis used the Paired Sample T-Test with the help of SPSS statistics 26. The results of the final data analysis test using the paired sample t-test stated that the Sig. (2-tailed) 0.000 0.05, meaning that in this study there was a difference in narrative essay writing skills between before and after using the cooperative learning model of cooperative integrated reading and composition. This is also supported by the average score obtained for the pretest, namely 48.58 and posttest, namely 80.04, so that the skill of writing narrative essays in class IV students at SD 1 Panggang before and after treatment has increased by 31.45 and has met the KKM. From the results of the data analysis, it can be concluded that there is an influence of the application of the CIRC type cooperative learning model on narrative essay writing skills in fourth grade students at SD N 1 Panggang.